A novel technique of aluminum multiplier slide culture for fungal identification - Lalita Matthapan (2019)
© 2018 Siriraj Medical Journal. Objective: Single slide culture technique (SSC) is the standard method of preparing fungal colonies for species identification. As contamination was frequently found, restarting the process wasted time and delayed diagnosis for patients. Aluminum slide culture (ASC) is the novel method, which aims to increase more fungal colonies in same time. Even through, some colonies showed contamination, there would be others left to use for identification. This study aimed to evaluate contaminate rate and time consumed in ASC technique to identify mold fungi compared to SSC. Methods: ASC and SSC were used to identify 50 fungal colonies comprising 3 species of dermatophytes including Trichophyton mentagrophytes, T. rubrum, Microsporum canis, and 2 species of non-dermatophytes including Neoscytalidium dimidiatum and Fusarium solani which are common causative molds for superficial fungal skin and nail infection. Fungal colonies were microscopically examined every 5 days. Time to species identification and contamination rate were recorded and analyzed. Results: This study demonstrated that ASC had equal efficacy in fungal identification with SSC. Median time from inoculation to fungal identification in ASC technique was 15 days which was significantly less than in SSC technique (18 days, p-value = 0.05). At 15 days after inoculation, contamination rate revealed 2% in ASC whereas in SSC it was significantly higher at 16%. Conclusion: ASC technique is an effective alternative method to prepare fungal colonies for identification. This study demonstrated that ASC uses less time to identify mold fungi and revealed lower contamination rate than SSC technique.